Response surface methodology study on the effects of sodium chloride and sodium tripolyphosphate concentrations, pressure level and holding time on beef patties properties - Szerman, Natalia; Ferrari, Romina; Sancho, Ana Maria; Vaudagna, Sergio Ramon (Elsevier, 2019)
A Box-Behnken design was applied to evaluate the effects of sodium chloride (NaCl, 0–2%) and sodium tripolyphosphate (STPP, 0–0.5%) concentrations, pressure level (100–300 MPa) and holding time (1–5min) on technological parameters, physicochemical and texture properties of beef patties. Patties were manufactured with lean beef (80%w/w), fat (10%w/w), water (10%w/w) and NaCl and STPP concentrations according to the design and were subjected to high hydrostatic pressure (HHP) treatments according the design. Raw and cooked patties pHs were modified by pressure level, NaCl and STPP concentration. Cooking loss increased when pressure level increased and additives concentrations decreased. NaCl and STPP concentrations and pressure level significantly modified colour parameters of raw patties; however, they had no effects on cooked patties. Moreover, texture parameters values increased with pressure level.